ANALISIS RESIKO PROYEK PADA PEKERJAAN JEMBATAN CISEPET CIKATOMAS DENGAN METODE FMEA - Juandi Lestari, Citra; Hendardi, Agi Rivi; Nurmayadi, Ade Rizky (JITSi : Jurnal Ilmiah Teknik Sipil, 2023)
Bridge construction involves uncertain risks, therefore it is necessary to carry out an analysis of all the risks that will occur, how big their impact will be (intensity), and the possibility of these risk events occurring. The method used is the Failure Mode and Effect Analysis (FMEA) method by determining severity, occurrence, detection where the results become RPN values and are determined by looking at the risk matrix table. From the risk matrix table above, conclusions can be drawn for high risk, namely the condition of the road to the project is steep, the project environment is less clean, the groundwater level is higher than the river, heavy equipment accidents, workers not wearing PPE, worker negligence and human resources not concentrating. For low risks, namely heavy equipment accidents, workers not wearing PPE and soft ground conditions. The results of the analysis using the FMEA method produced an RPN value of 64.00, it was found that 3 risk lists were included in the serious risk category and the highest risk value (NR) was 16, which was included in the high risk rating and required action to be taken. Keywords — Analysis, risk, project, Failure Mode and Effect Analysis (FMEA)   Abstrak—Konstruksi jembatan melibatkan risiko yang tidak pasti, oleh karena itu perlu untuk menganalisis semua risiko yang akan terjadi serta tingkat dampak dan kemungkinan risiko peristiwa. Metode yang digunakan dalam penelitian ini adalah Metode Failure Mode and Effect Analysis (FMEA) dengan menentukan tingkat keparahan, peristiwa, deteksi dimana hasilnya adalah nilai RPN dan ditentukan dengan melihat tabel matrik risiko. Hasil analisis menggunakan metode FMEA menghasilkan RPN nilai 64,00, ditemukan 3 daftar resiko yang jatuh ke kategori resiko serius dan nilai risiko tertinggi (NR) adalah 16 yang termasuk dalam peringkat risiko tinggi dan perlu ditangani. Kata kunci — Analisis, risiko, Failure Mode and Effect Analysis (FMEA)